2019
DOI: 10.1111/jdi.13038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety of insulin degludec/aspart (twice‐daily injections), insulin glargine 300 U/mL, and insulin glulisine (basal–bolus therapy)

Abstract: Aims/IntroductionWe compared the efficacy and safety of insulin degludec/aspart (IDegAsp) twice‐daily injections with insulin glargine 300 U/mL and insulin glulisine basal–bolus therapy (Gla300/Glu) using insulin glargine 300 U/mL (Gla300) and insulin glulisine (Glu).Materials and MethodsA total of 20 patients with type 2 diabetes mellitus were treated with IDegAsp twice‐daily injections; achievement of target preprandial glucose concentration of 100–130 mg/dL at breakfast and supper was determined using a wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…On the other hand, studies comparing IDegAsp once‐ to twice‐daily injection and basal bolus therapy have provided contradictory results. Among these, some studies found similar hypoglycaemia incidence rates, 9,12 whereas one study reported that IGlarU300 Insulin Glulisine basal‐bolus therapy had lower hypoglycaemia incidence rates compared to IDegAsp twice‐daily 13 . In our study, unlike in other studies, the insulin treatment of the patients using many different combinations was changed to IDegAsp twice‐daily injection.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…On the other hand, studies comparing IDegAsp once‐ to twice‐daily injection and basal bolus therapy have provided contradictory results. Among these, some studies found similar hypoglycaemia incidence rates, 9,12 whereas one study reported that IGlarU300 Insulin Glulisine basal‐bolus therapy had lower hypoglycaemia incidence rates compared to IDegAsp twice‐daily 13 . In our study, unlike in other studies, the insulin treatment of the patients using many different combinations was changed to IDegAsp twice‐daily injection.…”
Section: Discussionmentioning
confidence: 55%
“…However, Ozcelik et al found no significant change in FPG and HbA1c levels after switching from intensive insulin to IDegAsp 9 . By contrast, Kawaguchi et al used a blood glucose monitoring system showed that basal‐bolus therapy (IGlarU300—insulin glulisine) was superior to IDegAsp in terms of efficacy and safety 13 . Tsimikas et al reported that the administration of IDegAsp once‐ to twice‐daily injection showed similar efficacy in insulin intensification therapy when compared to multiple injection (basal‐bolus) therapy 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 12-week study comparing once-daily IDegAsp and basal insulin groups, HbA 1c change, daily insulin dose, and overall frequency of hypoglycaemia did not differ between the two groups [ 23 ]. Furthermore, Kawaguchi et al ., in their recently published study using the flash glucose monitoring system, demonstrated that the IGlar U300/insulin glulisine (basal-bolus treatment) was superior to IDegAsp in terms of efficacy and safety [ 24 ]. Our findings can be viewed as contradicting the previously held idea on the superiority of basal-bolus treatment over fixed-dose insulin preparations.…”
Section: Discussionmentioning
confidence: 99%